Índices de capacidad funcional, ansiedad y depresión en una muestra de adultos mayores de Santa Clara. / Index of functional capacity, anxiety and depression in a sample of older adults from Santa Clara. - Elizabeth Jiménez-Puig; Zoylen Fernández-Fleites; Yunier Broche-Pérez; José Carlos León-Ramos; Giselle Rodríguez-Carvajal; Roxana Rodríguez-Martín; Brayan Deivi Pérez-Leiva (Universidad de La Habana, 2021)
The objective of the present study was to characterize functional capacity, anxiety and depression in a group of older adults in the municipality of Santa Clara. From an intentional sampling and the determination of criteria for the conformation of the sample, this was formed by 69 elders belonging to the Home of Elders 1 "Marta Abreu", the House of Grandparents 2 "Camilo Cienfuegos", seniors who attend the University of the Elderly in Santa Clara and senior citizens belonging to the Family Medical Office 19. The sample presents homogeneous characteristics, there being a balance between the number of men and women. The evaluation was carried out, at first, by the application of the Barthel Index, the Geriatric Depression Scale and the Zung Anxiety Self-Assessment Scale. Subsequently semi-structured interviews were used for the qualitative stage of the process, which allowed deepening the indicators of anxiety and depression in part of the sample. The main results offered by the study were that in the majority of the subjects in the sample there is a presence of functional independence. Also, the great part of the sample selection does not present high rates of anxiety or depression due to factors such as the existence of support networks and social interaction. A relationship between female sex and higher rates of anxiety and depression was evidenced. A relationship was also observed between the non-existence of support networks and functional independence, as well as the reduction of anxious and depressive indices when the elderly has adequate family interaction. / RESUMEN El objetivo del presente trabajo fue caracterizar la capacidad funcional, la ansiedad y la depresión en un grupo de adultos mayores en el municipio de Santa Clara. La muestra estuvo conformada por 69 ancianos pertenecientes al Hogar de Ancianos 1 "Marta Abreu", la Casa de Abuelos 2 "Camilo Cienfuegos", adultos mayores que cursan la Universidad del Adulto Mayor en Santa Clara y adultos mayores pertenecientes al Consultorio Médico de la Familia, número 19. La muestra presentó características homogéneas, existiendo un equilibrio entre la cantidad de hombres y mujeres. La evaluación se llevó a cabo, en un primer momento, mediante la aplicación del Índice de Barthel, la Escala de Depresión Geriátrica y la Escala de Autovaloración de Ansiedad de Zung. Posteriormente se emplearon entrevistas semiestructuradas para la etapa cualitativa del proceso, que permitió profundizar en los indicadores de ansiedad y depresión en parte de la muestra. Los principales resultados ofrecidos por el estudio fueron que en la mayoría de los sujetos de la muestra existió presencia de independencia funcional. También que la gran parte de la selección muestral no presentó índices elevados de ansiedad o depresión debido a factores como la existencia de redes de apoyo y la interacción social. Se evidenció una relación entre el sexo femenino y mayores índices de ansiedad y depresión; también se observó una relación entre la no existencia de redes de apoyo y la independencia funcional, así como la disminución de los índices ansiosos y depresivos cuando el anciano cuenta con adecuada interacción familiar.